The king she shouldn't crave - Wight, Lela May (Harlequin presents, 2024)
"Their royal marriage: separate beds but shared temptation... Two months have passed since the world watched Natalia La Morte marry King Angelo Dizieno. But Natalia hasn't seen or heard from him since their startlingly scorching kiss at the altar... Promoted from spare to heir after tragedy struck, Angelo can't be distracted from his duty. Being within touching distance of the woman he has always craved--his brother's intended queen--has him on the precipice of self-destruction. The last thing he needs is for Natalia to recognize their dangerous attraction. If she does, there's nothing to stop it from becoming all-consuming..."--